Impact of personal control on user satisfaction - Kwon, Minyoung (A+BE | Architecture and the Built Environment, 2020)
Chapter 4 provided the impact of indoor climate on user satisfaction. Many studies reported that personal control over indoor environmental conditions is one of the influential factors for user satisfaction and environmental comfort due to its physical and psychological impacts. However, it is not clear to what extent users should be allowed to have control over the indoor environment. This chapter aims to identify the relationship between the extent to which users can personally control the conditions of their indoor environment and how satisfied they are with their thermal and visual comfort. Section 5.2 presents the data collection and assessment methods of occupants’ perceived satisfaction. The relationship between personal control and satisfaction is explained in section 5.3. Section 5.4 presents the dependency of user satisfaction with thermal comfort based on the degree of personal control over indoor environmental conditions, and section 5.5 explains the impact of the degree of person control on the user satisfaction with visual comfort. Section 5.6 discusses limitations of research of personal control, psychological impact of personal control, and how to design the personal control to optimise user satisfaction.